LIFE SKILLS FOR SUCCESS - WADKAR ALKA (NEW DELHI SAGE PUBLICATIONS PVT LTD, 2016)
This book is a comprehensive guide, written with a foundation in psychology, designed to help readers enhance their personal, social, and professional competence. It provides practical insights and application-oriented content to help individuals navigate the complexities of everyday life and achieve success.
Life Skills
Psychology
All Branches
Keywords: Life Skills; Psychology